The influence of the place and of the rite of the Holy Mass on the fulfilment of the festive precept - Kaniecki, Rafal (Prawo Kanoniczne, 2020)
The Council of Adge (506) decided that the festive precept could be fulfilled only in one’s own parish church. This rule spread to the Latin Church and survived until the Council of Trent (1545-1563). However previously it had been weakened by the customary law that allowed one to meet the obligation, in certain situations, in other parish churches, and also in churches of the mendicant orders, thanks to papal privileges. From the Council of Trent onwards, the faithful could only be encouraged to fulfil the precept in their own parish church. Moreover, they were allowed to do so in semi-private, semi-public oratories, in some private oratories, and also outside sacred places, participating in the Mass celebrated on the portable altars. In current legislation, it is enough to participate in the Mass celebrated in any place, but the Eucharistic celebration outside of the sacred place requires, for the lawfulness, the prior consent of the Ordinary. The festive precept is fulfilled through participation in the Mass celebrated in the Catholic rite. Since the nineteenth century, Latin and Eastern Catholics could fulfil it by participating in Mass in a different rite from their own. While the “Ecumenical Directory” (1967) had also admitted the possibility of fulfilling it occasionally through participation in the Mass celebrated by non-Catholics, the current “Ecumenical Directory” (1993) has expressly abrogated this privilege. Participation in the Catholic Mass celebrated by an excommunicated, interdicted, suspended priest, if his punishment is public, fulfils the festive precept, however a faithful can be punished with a just penalty for participation in it.